Clinical trials in cardiac xenotransplantation: Are we ready to overcome barriers? - Garcia, Leonardo Rufino [UNESP]; Brito, Flavio de Souza [UNESP]; Felicio, Marcello Laneza [UNESP]; Garzesi, André Monti [UNESP]; Tardivo, Márcia Terezinha [UNESP]; Polegato, Bertha Furlan [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Zornoff, Leonardo Antônio Mamede [UNESP] (Hindawi, 2021)
Heart allotransplantation has become one of the methods of choice in the treatment of severe heart failure. In the face of its difficulties, such as the unmet balance between organ supply and demand, the use of xenotransplantation (XTx) might be an attractive option shortly, even more with the ongoing progress achieved regarding the avoidance of hyperacute rejection and primary organ disfunction, maintenance of xenograft function and control of xenograft growth. To make possible this translational challenge, some points must be taken into account indeed, and they are the equipoise of human benefit and animal suffering, the risk of unknown infections, a well prepared informed consent, ethical and religious beliefs, and the role of cardiac XTx in a ventricular assistance device era.
Keywords: cardiovascular pathology; cardiovascular research; clinical review; transplant